Manual of retinal diseases : a guide to diagnosis and management - Medina, Carlos A.; Townsend, Justin H.; Singh, Arun D. (Springer, 2016)
This book is a comprehensive source of authoritative information on the clinical features, diagnosis, differential diagnosis, and management of medical and surgical retinal diseases. The Manual has 122 chapters, organized in 18 sections covering medical and surgical aspects of retinal diseases such as trauma, AMD, retinal inflammations, infections, endophthalmitis, pediatric diseases, dystrophies, and tumors. Easy-to-read chapters convey the fundamental concepts with the aid of clinical photographs, imaging studies (including fluorescein and indocyanineangiograms, ultrasonograms, CT scans, and MRI scans) and tables. The manual is of value to a wide range of practitioners and trainees, including students, residents, fellows and ophthalmologists who treat retinal diseases.